2006
DOI: 10.1063/1.2370880
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent surface CO stretching frequency investigations on nanodiamond particles

Abstract: In this work, the spectroscopic properties of surface functionalized nanodiamond particles are investigated via Fourier transform infrared spectroscopy. The functionalization of the nanodiamond surface was achieved chemically using strong acid treatment method. The size dependent C=O stretching frequency (between 1680 and 1820 cm(-1)) are studied for particle diameter sizes from the 5 to 500 nm range. The surface C=O stretching frequencies at approximately 1820 cm(-1), for large particle size (500 nm), down sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 39 publications
4
77
1
Order By: Relevance
“…The main signature of the effectiveness of the carboxylation process is the presence of the C À À À À O stretching band at around 1720-1740 cm À1 . It was previously reported that the central position of this band shifts from around 1725-1820 cm À1 depending on the NDs size in the 5-300 nm range [33]. Therefore, the observed band position confirms the 5 nm original size of the DNDs.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The main signature of the effectiveness of the carboxylation process is the presence of the C À À À À O stretching band at around 1720-1740 cm À1 . It was previously reported that the central position of this band shifts from around 1725-1820 cm À1 depending on the NDs size in the 5-300 nm range [33]. Therefore, the observed band position confirms the 5 nm original size of the DNDs.…”
supporting
confidence: 84%
“…The presence of a significant peak at 1728 cm À1 in the cNDs sample could be related to residues from the carboxylation process and also to the conversion of surface oxygenated groups to carboxylic acids [34]. The broad band around 3400 cm À1 and the band around 1630 cm À1 correspond to hydrogen-bonded-OH and O-H bending vibrations, respectively, attributed to adsorbed water on the ND surface [33,35]. The broad band near 3000 cm À1 can be ascribed to the CH stretching of the CH groups formed on the ND surface during the acid treatment [33].…”
mentioning
confidence: 95%
“…Treatment of the starting NDs in acidic media led to the introduction of functional groups onto their surface, as attested by the IR spectrum. [19,25] . [26] The band at 1575 cm À1 indicates the presence of primary amines, which are provided by APS.…”
Section: Resultsmentioning
confidence: 98%
“…FTIR spectra of these dried samples show the well-resolved line of C ¼ O stretching of carbonyl group on the nanodiamond surface in the range of 1720 to 1780 cm −1 as seen from the previous reports. 22 …”
Section: Nanodiamond Carboxylationmentioning
confidence: 99%
“…5,22 Fourier transform infrared (FTIR) Spectroscopy (Bomen MB 154, Canada) was used to analyze the cND's surface functional groups. FTIR spectra of these dried samples show the well-resolved line of C ¼ O stretching of carbonyl group on the nanodiamond surface in the range of 1720 to 1780 cm −1 as seen from the previous reports.…”
Section: Nanodiamond Carboxylationmentioning
confidence: 99%